Konsep Efikasi Diri dalam Perspektif Hadis - Minarni, Minarni; Ahmad, La Ode Ismail; Ali, Muhammad (Program Pascasarjana, UIN Alauddin Makassar, 2023)
Self-efficacy is a belief in which a person understands his or her abilities in solving certain problems or activities. Self-efficacy is belief in ability or competence for a given task. A person has confidence that they can achieve a goal, or overcome an obstacle. This belief in ability is influenced by dimensions and factors that influence a person's inner self-efficacy. Self-efficacy in the hadith perspective will give you the ability to become a strong person, to be an intelligent person, not to be a weak person, to be able to control your thoughts, to control yourself to take advantage of every opportunity, to control yourself to avoid bad thoughts, to avoid hasty attitudes, the ability to determining attitudes, the ability to restrain oneself (patience), the ability to behave in a way that makes things easier and builds an attitude of optimism. Abstrak Efikasi diri adalah keyakinan dimana seseorang memahami kemampuan yang dimilikinya dalam menyelesaikan masalah atau aktifitas tertentu. Efikasi diri adalah keyakinan akan kemampuan atau kompetensi atas tugas yang diberikan. Seseorang memiliki keyakinan dapat mencapai tujuan, atau mengatasi sebuah hambatan. Keyakinan akan kemampuan ini dipengaruhi oleh dimensi dan faktor yang mempengaruhi Efikasi diri dari dalam diri seseorang. Efikasi diri dalam persepektif hadis akan memberikan kemampuan menjadi pribadi yang tangguh, menjadi pribadi yang cerdas, tidak menjadi pribadi yang lemah, mampu dalam pengendalian amar, mengontrol diri untuk memanfaatkan setiap kesempatan, mengontrol diri untuk menghindari buruk sangka, menjauhi sikap tergesa-gesa, kemampuan menentukan sikap, kemampuan menahan diri (sabar), kemampuan untuk bersikap memberi kemudahan dan membangun sikap optimisme.